Effects of attentional focus and gaze instruction during observational learning of a basketball free-throw - Asadi, A.; Daneshfar, A.; Maleki, B.; Aiken, C. A. (Human Movement Science, 2023)
Observational learning has long been used to instruct individuals on how to perform a novice motor skill. Recently, research has shown a benefit to instructing learners to focus externally when viewing a video model (Asadi, Aiken, Heidari, & Kochackpour, 2021). Research has also highlighted the effectiveness of modeling correct gaze behaviors when learning a cognitive task (Jarodzka, van Gog, Dorr, Scheiter, & Gerjets, 2013). The purpose of the present study was to investigate the effectiveness of combining these two modalities. 40 individuals with a mean age of 21.77 ± 1.40 performed a novel motor task where they were asked to either focus internally or externally, and were provided with traditional instruction or were provided with an experienced performer's gaze behaviors while viewing a video demonstration. It was observed that both the external focus groups and the gaze instructed groups performed a basketball free-throw more accurately and had longer periods of quiet eye than an internal focus or traditional verbal instruction (p's < 0.05). Eye tracking also allowed for the assessment of attentional focus adherence. Participants focused on the instructed cues significantly more than irrelevant task aspects or a different focus types (p's < 0.05). These results highlight the effectiveness of cuing a learner to focus externally during observational learning. It also highlights the usefulness of providing correct gaze behaviors when observing a model.